(untitled) (Journal of Face Aesthetics, 2024)
The main theme of the conference will be physicality, psychicity, and mentality in facial aesthetics. Guests from the Netherlands, distinguished specialists in facial aesthetics Johan Jansma PhD, and Rutger Schepers PhD will focus on physicality. Their lectures will address issues related to aesthetic surgery of the forehead, eyebrows, and eyelids, as well as fillers and botulinum toxin since it is mostly an off‑label procedure in Poland. Lectures will also be presented by Polish distinguished professors: Prof. Leszek Kubisz, will reveal the secrets of biophysics in facial aesthetics, while Prof. Ewa Mojs, will show the importance of psychics in the psychological area, then Prof. Ewa Baum will consider mentality, that is, the influence of spirituality on facial beauty, Prof. Marzena Liliana Wyganowska, will present issues related to the possibility of using biostimulation and laser acupuncture. Lawyer Agnieszka Zemke‑Górecka PhD will highlight the problem, which concerns us all, of minors who use aesthetic medicine treatments. This part of the conference will be entirely in English with multimedia presentations in both English and Polish. After the lunch break, the lectures will begin in Polish but there will still be bilingual multimedia presentations. So, the next speakers: a guest from the Netherlands and also a graduate of our University, Artur Matthews‑Brzozowski PhD, will show the importance of maxillofacial surgery concerning facial aesthetics, and this will be continued by Oskar Komisarek also PhD. Next, Prof. Dorota Hojan‑Jezierska, will discuss aspects of hearing aid aesthetics, and Katarzyna Dubas PhD, an optometrist, will talk about the selection of eyeglass frames for facial aesthetics. Mentality in aesthetics is a broad topic, in terms of Eastern philosophy this aspect will be presented by Renata Zenobia Śleboda PhD. The issues raised at the end of the meeting are very important, often providing more questions than answers. Practical activities and workshops to promote the natural beauty of the face are also planned, at which it will be a pleasure to meet you.